Development of Textbooks for Sports Physiology Course in the Department of Physical Education and Health, State University of Malang - Andif Victoria; Pinton Setya Mustafa; M.E. Winarno (Universitas Muhammadiyah Enrekang, 2023)
The aim of this research is to created a product in the form of a sports physiology textbook for physical education and health students at the Faculty of Sports Science, State University of Malang. This research and development method includes: needs analysis, expert evaluation, small and large group product trials. Data analysis in this study used qualitative and descriptive quantitative percentage. The results of the evaluation by subject matter experts 79.6% good category, the results of small group trials 94.6% very good category, the results of large group trials 95.1% very good results. The conclusion obtained is that the sports physiology textbook product is suitable and can be used in courses in the department of physical education and health.